Deteksi Dini Profil Tekanan Darah Kader Kesehatan dan Warga Masyarakat - Gin Gin Sugih Permana; Tantri Puspita; Dian Roslan Hidayat; M. Ridwan Rifai; Eti Suliyati (Kilau Publishing, 2026)
Hypertension is a global health problem with high prevalence and is often undetected. This community service activity aimed to compare the blood pressure profile and demographic characteristics between Posyandu cadres and the general public in the working area of Karangpawitan and Tarogong Health Center as an early detection step for hypertension. The method used was direct blood pressure measurement and demographic data collection on 49 respondents divided into two groups: 33 Posyandu cadres and 16 community members. The results showed that the average age of cadres was 44.0 years (hypertension prevalence 36.4%), while the community members had an average age of 55.6 years (hypertension prevalence 56.3%). The community members had a much higher prevalence of hypertension, with a mean systolic blood pressure of 140.6 mmHg compared to 131.9 mmHg in cadres. This activity concluded that although both groups have a high risk of hypertension, the public (especially the elderly) has a higher prevalence and requires more intensive screening interventions, while cadres still require regular monitoring to remain healthy as health promoter agents.